FMEA and Statistical Process Control in Identifying Cause of Black Dot Injection Pipe - Rohana, Rohana; Herlambang, Hendi; Simon, Gusman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
PT UII is a manufacturing company that produces spare parts for two-wheeled and four-wheeled vehicles. From 2023 to 2024, the peak of the problem occurred in the Pipe Injection product for Gasoline Direct Injection (GDI) products, namely the Black Dot problem. This problem has been reported to the parent company, PT UII JPN, and it has been decided that this problem is a challenge for the PT UII group that cannot be completely eliminated by 2024. This problem has caused significant losses for PT UII. Black Dot on the end forming part of the pipe is caused by contamination during the annealing process on the end forming part, where the end forming part is treated to achieve a certain level of softness through a heating process. The Black Dot problem is the problem that causes the most losses for PT UII. Based on observations from 2024 to January 2025, improvements are needed using fishbone diagram analysis and FMEA evaluation of the annealing process. The fishbone diagram is a method used to identify the factors causing the black dot problem, and FMEA is a system designed to maintain control over the production process, aiming to determine the highest risk level for problems occurring in the production process and prepare corrective actions for each process.